Microsoft Office Training for Village Officials to Improve Computer Skills - Ade Risna Sari; Dedy Suryadi; Rulam Ahmadi; Ekbal Santoso; Eko Meiningsih Susilowati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
A community service project called "Microsoft Office Utilisation Training in Cimekar Village to Improve Computer Skills for Village Apparatuses and Karang Taruna Management" aims to help village officials and youth organisations in Cimekar Village manage village administrative tasks more effectively. Not all village elders and youth committee members currently possess Microsoft Office proficiency. Many of them still have trouble using programmes like Microsoft Word and Excel. This act of community service was performed at the Cimekar Village Office Meeting Hall in the Cileunyi District of Bandung Regency on May 18–20, 2023. Setting goals and objectives, identifying and analysing issues or needs, choosing teams, coordinating with relevant parties, providing necessary resources, as well as creating implementation schedules, assessment procedures, and the final report, were all part of the planning process.